Performance optimization SYSTEM FOR USING THE WORLD INDUSTRIES PLC - Syahril Syahril Syahril (JAKSTIK Journal, 2003)
PLC at the beginning of his birth is known as a Programmable Controller (PC), known as theproduct of a project with a view to obtaining a compact instrument that can be programmedand direprogram like computers, do not take place as well as energy-based digital technology,which can replace a relay circuit complex, rigid (hard-wired, inflexible) and takes place aswell as a large energy. Meanwhile, a series of relays in question are the backbone ofindustrial control systems and manufacturing processes. In other words, today's PLC productsis actually departing from the need to run the industry to be more cheaply and efficiently.